Prospective of wind and solar photovoltaic energy for electricty production - Beltrán-Telles, Aurelio (Universidad Autónoma de Tamaulipas, 2017)
The increase in the price of fossil fuels and the pollution problems arising from their burning has resulted in the intensification of the use of renewable energy sources to produce electricity. The purpose of this study was to estimate the development of solar photovoltaic and wind energy in electricity generation, compared to the generation produced with fossil fuels. Several reports issued by governmental and non-governmental bodies on global energy consumption to produce electricity from fossil fuels and from renewable energy sources, on climate change and on policies to incorporate renewable energy sources in the global energy portfolio were consulted. The results indicated that electric power from wind and solar photovoltaic energy generation plants are competitive with respect to the plants that use fossil resources. In the short run, regulatory laws that include pollution-related sanctions to limit the effects on climate change are expected to emerge. Such laws are likely to raise the cost of production of conventional plants, while favoring the development of renewable energy plants, mainly solar photovoltaic, which has the fastest growing renewable energy.